The early settlement of Northern Europe. (18th February 2019) - Robson, Harry K.
Abstract : This three-volume publication presents an up-to-date overview on the human colonisation of Northern Europe across the Pleistocene–Holocene transition in Scandinavia, the Eastern Baltic and Great Britain. Volume 1, Ecology of early settlement in Northern Europe, is a collection of 17 articles focusing on subsistence strategies and technologies, ecology and resource availability and demography in relation to different ecological niches. It is structured according to three geographic regions, the Skagerrak-Kattegat, the Baltic Region and the North Sea/Norwegian Sea, while its temporal focus is Late Glacial and Postglacial archaeology, c . 11000–5000 cal BC. These regions are particularly interesting given the long research history, which goes back as far as the nineteenth century (see Gron & Rowley-Conwy 2018), and the numerous environmental changes that have taken place throughout the Holocene: the presence of ice until c . 7500 cal BC, isostatic rebound alongside sea-level rise and the formation of the Baltic Sea, all of which have contributed to the preservation of outstanding archaeology.